ISO 27001 controls : a guide to implementing and auditing - Kenyon, Bridget (IT Governance Publishing, 2019)
Ideal for information security managers, auditors, consultants and organizations preparing for ISO 27001 certification, this book will help readers understand the requirements of an ISMS (information security management system) based on ISO 27001. --